2018
DOI: 10.2116/analsci.18p433
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycols for the Dispersion Development of Graphene in an Aqueous Surfactant Solution Studied by Affinity Capillary Electrophoresis

Abstract: Water-soluble nonionic polymers of polyethylene glycol (PEG), poly(vinyl alcohol) (PVA), and polyvinylpyrrolidone (PVP) were examined to develop the dispersion of graphene in an aqueous surfactant solution. Sodium dodecylbenzenesulfonate was used as an anionic surfactant to disperse graphene in an aqueous solution and to give negative charge on it. The dispersion of graphene was monitored through the electropherograms in affinity capillary electrophoresis; a broad peak for the dispersed graphene and shot signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The sharpness of the peak is distinct from the peak shape of CZE or MEKC signals of graphene. [17][18][19] The result suggests that the major component of BG-CND is rather uniform; the mass/charge ratio is not so much dispersed. Markova, et al have detected a similar sharp peak for core-shell CNDs by fluorimetric detection.…”
Section: Capillary Zone Electrophoresis Of the Cndsmentioning
confidence: 95%
“…The sharpness of the peak is distinct from the peak shape of CZE or MEKC signals of graphene. [17][18][19] The result suggests that the major component of BG-CND is rather uniform; the mass/charge ratio is not so much dispersed. Markova, et al have detected a similar sharp peak for core-shell CNDs by fluorimetric detection.…”
Section: Capillary Zone Electrophoresis Of the Cndsmentioning
confidence: 95%
“…Various functional electrodes containing CNTs have been developed . Dispersion is necessary to fabricate homogeneous CNT films on the electrode surface because CNTs are insoluble, and water‐soluble polymers have been used as dispersants for CNTs . CNT‐modified electrodes have been fabricated by dropping a dispersion of CNTs in water‐soluble polymers onto the electrode and drying it .…”
Section: Figurementioning
confidence: 99%
“…This method is commonly used because it is simple, low‐cost, and does not require special equipment. The water‐soluble polymers polystyrene sulfonate (PSS), polyethylenimine (PEI), polyvinylpyrrolidone (PVP), and poly(vinyl alcohol) (PVA) have been used as dispersants (Figure ).…”
Section: Figurementioning
confidence: 99%
“…Takayanagi et al reported that the dispersion of graphene in an aqueous solution containing water-soluble polymers and anionic surfactants was monitored by CE. 9,10 They found that the number of shot signals was reduced and a broad peak of the dispersed graphene became narrower upon the addition of PEG and dodecylbenzenesulfonate in a separation buffer. Yamamoto et al reported on a concurrent analysis of inorganic anions and cations filled in a whole capillary in CE-C 4 D. 11 Under a suppressed EOF, the migrations of anions and cations to different polarities gave a stepwise electropherogram.…”
mentioning
confidence: 99%